The major threats to the Endangered Barbary macaque Macaca sylvanus in North Africa - Abderrazak El Alami; Els Van Lavieren; Abderrahman Chait (European Journal of Ecology, 2022)
The Barbary macaque is currently the only macaque species that occurs beyond Asia. It has been classified as an endangered species on the IUCN’s Red List and is listed in CITES Appendix I. This species is actually restricted to small and fragmented habitats in the Moroccan Rif, Middle and High Atlas, and in the Algerian areas of Chiffa, Grande Kabylie and the Petite Kabylie. A very large number of studies indicated that this primate is in decline and its population is estimated to have declined at a rate exceeding 50% over the last three generations. This article aims to review the major threats and challenges to the Barbary macaque conservation in North Africa. Data were gathered from research articles, scientific books, communications, thesis and PhD dissertations of the authors and of other researchers. Results showed that the major threats to the survival of Barbary macaques are habitat loss and degradation, population fragmentation, capture and trade of macaques, effects of human activities on Barbary macaques’ behavior and ecology, conflict with inhabitants due to crop raiding, the decrease in water availability to macaques, and infectious disease risks. Based on this review, we recommend several measures to reduce the likelihood of the Barbary macaque becoming extinct in many regions of North Africa.